Reduced lung function due to biomass smoke exposure in young adults in rural Nepal. - Kurmi, O; Devereux, G; Smith, W; Semple, S; Steiner, M; Simkhada, P; Lam, K; Ayres, J (2013)
This study aimed to assess the effects of biomass smoke exposure on lung function in a Nepalese population, addressing some of the methodological issues seen in previous studies. We carried out a cross-sectional study of adults in a population exposed to biomass smoke and a non-exposed population in Nepal. Questionnaire and lung function data were acquired along with direct measures of indoor and outdoor air quality. Ventilatory function (forced expiratory volume in 1 s (FEV(1)), forced vital capacity (FVC) and forced expiratory flow at 25-75% of FVC) was significantly reduced in the population using biomass across all age groups compared to the non-biomass-using population, even in the youngest (16-25 yrs) age group (mean FEV(1) (95% CI) 2.65 (2.57-2.73) versus 2.83 (2.74-2.91) L; p=0.004). Airflow obstruction was twice as common among biomass users compared with liquefied petroleum gas users (8.1% versus 3.6%; p<0.001), with similar patterns for males (7.4% versus 3.3%; p=0.022) and females (10.8% versus 3.8%; p<0.001), based on the lower limit of normal. Smoking was a major risk factor for airflow obstruction, but biomass exposure added to the risk. Exposure to biomass smoke is associated with deficits in lung function, an effect that can be detected as early as the late teenage years. Biomass smoke and cigarette smoke have additive adverse effects on airflow obstruction in this setting.